Immuno-Biochemical Impacts of Gamma Irradiation in Male Rats: A Dose-Response Study - Soha M. Hussien; Engy R. Rashed (SAGE Publishing, 2023)
During radiotherapy, immune-modulatory effects of radiation doses should be taken into consideration, not only the anti-tumor radiation effects. Thus, our study aimed to study how γ-radiation modulates immune response in comparison to common immune-suppressive/stimulant agents. Animals were divided into two groups. Category A received Echinacea purpura extract (EP) or irradiated at low radiation doses 0, .25 or .5 Gray (Gy), whereas Category B received cyclophosphamide (CP) or irradiated at high radiation doses 1, 2, or 5 Gy. Serum levels of immunological mediators interleukin-10 (IL-10) and tumor necrosis factor (TNF-α), as well as redox-markers malondialdehyde (MDA) and nitric oxide (NO), hemoglobin (Hgb), white and red blood cells (WBCs, RBCs), and platelet counts were assessed following irradiation. Of the immune-stimulant category, .25 Gy dose offered EP-comparable effects in TNF-α, RBCs, Hgb, and platelet counts cases. As for the immune-suppressive category; 5 Gy irradiation dose induced inflammatory/immunosuppressive responses indicated (rise in NO, TNF-α, and IL-10), and an oxidative stress status (increase in serum MDA). However, 5 Gy γ-irradiation was not observed, herein, as a single immunosuppressive agent. To conclude, during radiotherapy, immunological impact(s) of the used radiation doses should be optimized and followed-up closely to assess the risk/benefit of their usage.